Ultralow detection limit and ultrafast response/recovery of the H2 gas sensor based on Pd-doped rGO/ZnO-SnO2 from hydrothermal synthesis - Zhang, Xinxiao; Sun, Jianhai; Tang, Kangsong; Wang, Hairong; Chen, Tingting; Jiang, Kaisheng; Zhou, Tianye; Quan, Hao; Guo, Ruihua (Microsystems & nanoengineering, 2022)
Hydrogen (H 2 ) sensors are of great significance in hydrogen energy development and hydrogen safety monitoring. However, achieving fast and effective detection of low concentrations of hydrogen is a key problem to be solved in hydrogen sensing. In this work, we combined the excellent gas sensing properties of tin(IV) oxide (SnO 2 ) and zinc oxide (ZnO) with the outstanding electrical properties of reduced graphene oxide (rGO) and prepared palladium (Pd)-doped rGO/ZnO-SnO 2 nanocomposites by a hydrothermal method. The crystal structure, structural morphology, and elemental composition of the material were characterized by FE-SEM, TEM, XRD, XPS, Raman spectroscopy, and N 2 adsorption–desorption. The results showed that the Pd-doped ZnO-SnO 2 composites were successfully synthesized and uniformly coated on the surface of the rGO. The hydrogen gas sensing performance of the sensor prepared in this work was investigated, and the results showed that, compared with the pure Pd-doped ZnO-SnO 2 sensor, the Pd-doped rGO/ZnO-SnO 2 sensor modified with 3 wt% rGO had better hydrogen (H 2 )-sensing response of 9.4–100 ppm H 2 at 380 °C. In addition, this sensor had extremely low time parameters (the response time and recovery time for 100 ppm H 2 at 380 °C were 4 s and 8 s, respectively) and an extremely low detection limit (50 ppb). Moreover, the sensor exhibited outstanding repeatability and restoration. According to the analysis of the sensing mechanism of this nanocomposite, the enhanced sensing performance of the Pd-doped rGO/ZnO-SnO 2 sensor is mainly due to the heterostructure of rGO, ZnO, and SnO 2 , the excellent electrical and physical properties of rGO and the synergy between rGO and Pd.